1,4-Dipolar cycloaddition in organic synthesis: a facile route to isoquinoline fused heterocycles - Nair, Vijay; Sreekanth, Anakkalil R.; Abhilash, N.; Biju, Akkattu T.; Varma, Luxmi; Viji, Sreemathi; Mathew, Saumini (Arkivoc, 2005)
The three component condensation reactions involving isoquinoline, dimethyl acetylenedicarboxylate and carbonyl dipolarophiles such as o- and p-benzoquinones and Nsubstituted isatins constitute a one-pot synthesis of a variety of [1,3]oxazino isoquinoline derivatives via 1,4-dipolar cycloaddition.

One pot four component reaction of isocyanides, dimethyl acetylenedicarboxylate and cyclobutene-1,2-diones: synthesis of spiro heterocycles - Nair, Vijay; Menon, Rajeev S.; Deepthi, Ani B.; Devi, Rema; Biju, Akkattu T. (Tetrahedron Letters, 2005)
Isocyanides, dimethyl acetylenedicarboxylate, and cyclobutene-1,2-diones react in one-pot to afford novel spirocyclic compounds with double insertion of the isocyanide.

Reaction of diaryl-1,2-diones with triphenylphosphine and diethyl azodicarboxylate leading to N, N-dicarboethoxy monohydrazones via a novel rearrangement - Nair, Vijay; Biju, Akkattu T.; Abhilash, K. G.; Menon, Rajeev S.; Eringathodi, Suresh (Organic Letters, 2005)
A mechanistically novel reaction of diaryl-1,2-diones with diethyl azodicarboxylate and triphenylphosphine to afford N,N-dicarboethoxy monohydrazones is described. The reaction proceeds via a nitrogen to nitrogen migration of a carboethoxy group.

Reaction of huisgen zwitterion with 1,2-benzoquinones and isatins: expeditious synthesis of dihydro-1,2,3-benzoxadiazoles and spirooxadiazolines - Nair, Vijay; Biju, Akkattu T.; Vinod, A. V.; Eringathodi, Suresh (Organic Letters, 2005)
The zwitterionic intermediate generated from dialkyl azodicarboxylate and triphenylphosphine on reaction with 3-methoxy-1,2-benzoquinones afforded dihydro-1,2,3-benzoxadiazoles. N-Substituted isatins furnished spirooxadiazolines under similar conditions.

DMAP-catalyzed reaction of beta-ketoesters and dimethyl acetylenedicarboxylate: an efficient synthesis of polysubstituted benzenes and biaryls - Nair, Vijay; Vidya, N.; Biju, Akkattu T.; Deepthi, Ani B.; Abhilash, K. G.; Eringathodi, Suresh (Tetrahedron, 2006)
A DMAP catalyzed tandem addition–cyclization–dehydration sequence involving dimethyl acetylenedicarboxylate and β-ketoesters leading to polysubstituted benzene/biaryl derivatives is presented.

Engaging zwitterions in carbon-carbon and carbon-nitrogen bond- forming reactions: a promising synthetic strategy - Nair, Vijay; Menon, Rajeev S.; Sreekanth, A. R.; Abhilash, N.; Biju, Akkattu T. (Accounts of Chemical Research, 2006)
An Account of carbon−carbon and carbon−nitrogen bond-forming reactions mediated by zwitterions generated by the addition of organic nucleophiles to activated unsaturated systems highlighting their synthetic potential is presented.

Novel synthesis of highly functionalized pyrazolines and pyrazoles by triphenylphosphine mediated reaction of dialkyl azodicarboxylate with allenic esters - Nair, Vijay; Biju, Akkattu T.; Mohanan, Kishor; Eringathodi, Suresh (Organic Letters, 2006)
Reaction of the Huisgen zwitterion, derived from triphenylphosphine and dialkyl azodicarboxylate, with allenic esters affords highly functionalized pyrazolines and pyrazoles. The crystal structure of pyrazoline derivative 7a showed extensive C−H···O interactions. Pyrazole formation proceeds via a novel nitrogen to carbon migration of the carboalkoxy group.

Efficient higher-order cycloaddition reactions of 8,8-dicyanoheptafulvenes with dienes - Nair, Vijay; Gopalakrishnan Abhilash, K.; Biju, Akkattu T.; Eringathodi, Suresh (Synthesis-Stuttgart, 2007)
The cycloaddition reactions of 8,8-dicyanoheptafulvene with electron-rich dienes afforded the higher order cycloaddition products in excellent yields. With cyclic dienes as well as dimethoxybutadiene the [8+2] adducts were obtained exclusively. With methyl- and dimethylbutadienes the [6+4] adducts were the only products isolated.
Keywords: cycloadditions - bicyclic compounds - polycycles - dicyanoheptafulvene - tetrahydroazulenes

Novel reaction of the “huisgen zwitterion” with chalcones and dienones: an efficient strategy for the synthesis of pyrazoline and pyrazolopyridazine derivatives - Nair, Vijay; Biju, Akkattu T.; Mathew, Smitha C.; Eringathodi, Suresh (Angewandte Chemie-International Edition, 2007)
Two unexpected transformations: The reaction of the Huisgen zwitterion derived from triphenylphosphane and diisopropyl azodicarboxylate (DIAD) with chalcones affords functionalized pyrazolines. In contrast, the reaction with dienones affords pyrazolopyridazines, presumably by Diels–Alder reaction of the initially formed pyrazoline with excess DIAD (see scheme).
Keywords: chalcones; nitrogen heterocycles; pyrazolines; synthetic methods; zwitterions

Reaction of huisgen zwitterion with diaryl-1,2-diones and ketones: an efficient protocol for carbon-nitrogen bond formation - Nair, Vijay; Biju, Akkattu T.; Mathew, Smitha C. (Synthesis-Stuttgart, 2007)
The reaction of Huisgen zwitterion, derived from triphenylphosphine and dialkyl azodicarboxylate, with diaryl-1,2-diones afforded N,N-dicarboalkoxy monohydrazones via a mechanistically novel rearrangement. Cyclic and acyclic ketones furnished vinyl hydrazinedicarboxylates under similar conditions.
Keywords: betaines - diazo compounds - hydrazones - ketones - rearrangements

Reaction of tpp-azodicarboxylate zwitterions and aldehydes: unprecedented synthesis of acyl carbamates - Nair, Vijay; Mathew, Smitha C.; Biju, Akkattu T.; Eringathodi, Suresh (Tetrahedron Letters, 2007)
An efficient synthesis of acyl carbamates from aryl aldehydes by the reaction of triphenylphosphine and dialkyl azoesters is described.

Stereoselective synthesis of 3,4-trans-disubstituted γ-lactams by cerium(iv) ammonium nitrate mediated radical cyclization of cinnamamides - Nair, Vijay; Mohanan, Kishor; Suja, Tachapully D.; Biju, Akkattu T. (Synthesis-Stuttgart, 2007)
A facile synthesis of 3,4-trans-disubstituted γ-lactams was developed, consisting of the radical cyclization of cinnamamides mediated by cerium(IV) ammonium nitrate. The single-electron-transfer (SET) reaction of the methoxystyrenyl moiety mediated by cerium(IV) ammonium nitrate gives rise to a cation radical, whose cyclization followed by reaction with oxygen and methanol generates 3,4-trans-disubstituted γ-lactams.
Keywords: cerium(IV) ammonium nitrate - intramolecular cyclization - cinnamamides - single electron transfer - γ-lactams

Carbon-nitrogen bond-forming reactions of dialkyl azodicarboxylate: a promising synthetic strategy - Nair, Vijay; Biju, Akkattu T.; Mathew, Smitha C.; Pattoorpadi, Beneesh Babu (Chemistry an Asian Journal, 2008)
Azodicarboxylates have found applications in electrophilic amination reactions and in pericyclic reactions. The nucleophilic trigger in Mitsunobu reactions, that is, the zwitterion formed from triphenylphosphine and dialkyl azodicarboxylate, has been utilized recently in various heterocyclic constructions. This Focus Review summarizes the potential utility of azodicarboxylates in various carbon–nitrogen bond-forming reactions.
Keywords: amination reactions; azodicarboxylates; C[BOND]N bond formation; heterocycles; Huisgen zwitterion

Reaction of huisgen zwitterion with diaryl ketones leading to the facile synthesis of mono- and bis(alkoxycarbonyl)hydrazones - Nair, Vijay; Mathew, Smitha C.; Biju, Akkattu T.; Eringathodi, Suresh (Synthesis-Stuttgart, 2008)
The Huisgen zwitterion, generated from triphenylphosphine and dialkyl azodicarboxylates, afforded upon reaction with diaryl ketones both mono- and bis(alkoxycarbonyl)hydrazones, depending on the reaction conditions.

Copper-catalyzed synthesis of 2-unsubstituted, n-substituted benzimidazoles - Hirano, Keiichi; Biju, Akkattu T.; Glorius, Frank (Journal of Organic Chemistry, 2009)
An efficient copper-catalyzed intramolecular arylation of formamidines forming 2-unsubstituted benzimidazoles in excellent yields is reported. Sixteen examples bearing sterically demanding substituents on nitrogen like Mes, 2,6-diisopropylphenyl, or 2-tert-butylphenyl and tolerating various functional groups demonstrate the utility of this method.

N-heterocyclic carbene-catalyzed hydroacylation of unactivated double bonds - Hirano, Keiichi; Biju, Akkattu T.; Piel, Isabel; Glorius, Frank (Journal of the American Chemical Society, 2009)
An intramolecular N-heterocyclic carbene (NHC)-catalyzed hydroacylation of unactivated double bonds is reported. Systematic variation of the catalyst structure revealed an N-mesitylthiazolylidene annulated with a seven-membered ring to be especially reactive. This NHC enables a unique C−C bond-forming reaction to afford substituted chroman-4-ones in moderate to excellent yields, even ones containing all-carbon quaternary centers.

Polymeric ladderphanes - Chou, Chih-Ming; Lee, Shern-Long; Chen, Chih-Hsien; Biju, Akkattu T.; Wang, Hsian-Wen; Wu, Yi-Lin; Zhang, Guo-Fu; Yang, Kuang-Wei; Lim, Tsong-Shin; Huang, Min-Jie; Tsai, Po-Yu; Lin, Kin-Chuan; et al. (Journal of the American Chemical Society, 2009)
A new class of polymers, which have a double-stranded polybinorbornene skeleton with multilayer planar oligoaryl linkers, defined as polymeric ladderphanes, are synthesized. The structures of these ladderphanes are determined by spectroscopic means. Photophysical studies and time-resolved fluorescence spectroscopic investigations reveal that there is a strong interaction between the chromophore linkers. Thus, Soret band splitting in the absorption spectrum of the polymer with porphyrin linker (12e), significant fluorescence quenching with oligoaryl linkers (12b−d), and excimer emission with a terphenylene-diethynylene linker (12a) are characteristic photophysical properties of these polymers. Scanning tunneling microscopy shows that polymers 12b and d exhibit a ladder-like morphology and form a supramolecular assembly leading to a two-dimensional ordered array on a highly oriented pyrolytic graphite surface.

Reactions of morita-baylis-hillman acetates with huisgen zwitterions: a novel strategy for the synthesis of ?-amino acid derivatives - Jose, Anu; Paul, Rony Rajan; Mohan, Resmi; Mathew, Smitha C.; Biju, Akkattu T.; Eringathodi, Suresh; Nair, Vijay (Synthesis, 2009)
The reaction of Huisgen Zwitterion with Morita–Baylis– Hillman acetates afforded b-amino acid derivatives.
Keywords: b-amino acid; Huisgen zwitterion; Morita–Baylis–Hillman acetate

Switching the electron-donor properties of n-heterocyclic carbenes by a facile deprotonation strategy - Biju, Akkattu T.; Hirano, Keiichi; Frohlich, Roland; Glorius, Frank (Chemistry an Asian Journal, 2009)
Flip the switch! The facile and distinct variation of the electronic properties of an N-heterocyclic carbene (NHC) ligand is reported. In this process, a simple deprotonation/protonation strategy can render the NHC to be an electron-poor or an electron-rich NHC ligand: one ligand, two electronic natures.
Keywords: carbenes; electronic properties; enolates; heterocycles; ligand design

Intermolecular N-heterocyclic carbene-catalyzed hydroacylation of arynes - Biju, Akkattu T.; Glorius, Frank (Angewandte Chemie-International Edition, 2010)
A formal introduction: The conceptually new N-heterocyclic carbene catalyzed formal insertion of arynes into the Cformyl[BOND]H bond of aldehydes demonstrates the compatibility of nucleophilic NHCs with electrophilic arynes. This NHC-catalyzed hydroacylation of arynes allows the conversion of aliphatic, α,β-unsaturated, and aromatic aldehydes into aryl ketones; 27 examples and a preliminary mechanistic investigation are provided.

N-heterocyclic carbene-catalyzed cascade reaction involving the hydroacylation of unactivated alkynes - Biju, Akkattu T.; Wurz, Nathalie E.; Glorius, Frank (Journal of the American Chemical Society, 2010)
The N-heterocyclic carbene (NHC)-catalyzed hydroacylation of unactivated alkynes to provide α,β-unsaturated ketones is reported. In addition, a rare case of an efficient and selective dually NHC-catalyzed cascade reaction involving the hydroacylation of alkynes and a subsequent intermolecular Stetter reaction allows the formation of chromanones containing a 1,4-diketone moiety.

Efficient synthesis of benzofuranones: N-heterocyclic carbene (NHC)/base-catalyzed hydroacylation-stetter-rearrangement cascade - Padmanaban, Mohan; Biju, Akkattu T.; Glorius, Frank (Organic Letters, 2011)
A N-heterocyclic carbene/base-catalyzed cascade reaction leading to the formation of functionalized benzofuranones is reported. The reaction proceeds via an intramolecular hydroacylation of unactivated alkynes followed by an intermolecular Stetter reaction and a base-catalyzed chromanone to benzofuranone rearrangement.

Employing homoenolates generated by NHC catalysis in carbon-carbon bond-forming reactions: state of the art - Nair, Vijay; Menon, Rajeev S.; Biju, Akkattu T.; Sinu, C. R.; Paul, Rony Rajan; Jose, Anu; Sreekumar, Vellalath (Chemical Society Reviews, 2011)
Homoenolate is a reactive intermediate that possesses an anionic or nucleophilic carbon beta to a carbonyl group or its synthetic equivalent. The recent discovery that homoenolates can be generated from alpha,beta-unsaturated aldehydes via N-Heterocyclic Carbene (NHC) catalysis has led to the development of a number of new reactions. A majority of such reactions include the use of carbon-based electrophiles, such as aldehydes, imines, enones, dienones etc. resulting in the formation of a variety of annulated as well as acyclic products. The easy availability of chiral NHCs has allowed the development of very efficient enantioselective variants of these reactions also. The tolerance showed by NHCs towards magnesium and titanium based Lewis acids has been exploited in the invention of cooperative catalytic processes. This tutorial review focuses on these and other types of homoenolate reactions reported recently, and in the process, updates the previous account published in 2008 in this journal.

Extending nhc-catalysis: reaction of aldehydes with unconventional reaction partners - Biju, Akkattu T.; Kuhl, Nadine; Glorius, Frank (Accounts of Chemical Research, 2011)
Transition metal catalysis is a powerful means of effecting organic reactions, but it has some inherent drawbacks, such as the cost of the catalyst and the toxicity of the metals. Organocatalysis represents an attractive alternative and, in some cases, offers transformations unparalleled in metal catalysis. Unique transformations are a particular hallmark of N-heterocyclic carbene (NHC) organocatalysis, a versatile method for which a number of modes of action are known. The NHC-catalyzed umpolung (that is, the inversion of polarity) of electrophilic aldehydes, through formation of the nucleophilic Breslow intermediate, is probably the most important mode of action. In this Account, we discuss the reaction of Breslow intermediates with unconventional reaction partners.

N-Heterocyclic carbene catalyzed umpolung of michael acceptors for intermolecular reactions - Biju, Akkattu T.; Padmanaban, Mohan; Wurz, Nathalie E.; Glorius, Frank (Angewandte Chemie-International Edition, 2011)
eahciM! The N-heterocyclic carbene catalyzed umpolung of Michael acceptors proceeds through the formation of a deoxy-Breslow intermediate (see scheme; EWG=electron-withdrawing group). This nucleophilic species can react with other Michael acceptors in an intermolecular fashion, thereby resulting in the formation of homo- or heterodimeric olefins. This “Michael umpolung” should become a valuable method for the formation of densely functionalized olefins.
Keywords: carbenes; Michael acceptors; nitrogen heterocycles; organocatalysis; umpolung

N-heterocyclic carbene-catalyzed cross-coupling of aromatic aldehydes with activated alkyl halides - Padmanaban, Mohan; Biju, Akkattu T.; Glorius, Frank (Organic Letters, 2011)
N-Heterocyclic carbene-catalyzed umpolung of aldehydes followed by their interception with diarylbromomethanes has been reported. This conceptually novel transition-metal-free cross-coupling of aldehydes with alkyl halides works well at low catalyst loadings and under mild reaction conditions leading to the formation of diaryl acetophenone derivatives in good yields. In addition, α-halo ketones and esters can also be used as aldehyde reaction partners.

Organocatalytic asymmetric 1,6-addition reactions - Biju, Akkattu T. (Chemcatchem, 2011)
Keywords: Asymmetric synthesis; catalysis; Michael addition; organocatalysis; phase-transfer catalysis

Synthesis and application of a chiral diborate - Loewer, Yvonne; Weiss, Christine; Biju, Akkattu T.; Frohlich, Roland; Glorius, Frank (Journal of Organic Chemistry, 2011)
A chiral diborate with different counterions is reported whose structure was unambiguously confirmed by X-ray analysis. This chiral dianion was used in the resolution of trans-1,2-diamines and also as a chiral shift reagent for NMR analysis of triphenylphosphonium salts.

1,2-Benzoquinones in Diels-Alder reactions, dipolar cycloadditions, nucleophilic additions, multicomponent reactions and more - Nair, Vijay; Menon, Rajeev S.; Biju, Akkattu T.; Abhilash, K. G. (Chemical Society Reviews, 2012)
A brief account of the recent developments in the chemistry of 1,2-benzoquinones is presented in this tutorial review. The title compounds exhibit commendable versatility in both Diels-Alder and dipolar cycloaddition reactions. They have also been employed as electrophilic reaction partners in nucleophile-triggered catalytic processes and related multicomponent reactions. These, along with other reactions described here, lead to the synthesis of densely functionalised carbocyclic and heterocyclic frameworks that are otherwise difficult to access.

Arynes in transition-metal-free multicomponent coupling reactions - Bhojgude, Sachin Suresh; Biju, Akkattu T. (Angewandte Chemie-International Edition, 2012)
Let's couple together! The multicomponent reactions involving arynes offer direct access to unusual heterocyclic scaffolds and 1,2-disubstituted arenes. This transition-metal-free, one-pot construction of molecular complexity is likely to play a pivotal role in various carbon–carbon and carbon–heteroatom bond-forming reactions.

Efficient diels-alder reaction of 1,2-benzoquinones with arynes and its utility in one-pot reactions - Kaicharla, Trinadh; Bhojgude, Sachin Suresh; Biju, Akkattu T. (Organic Letters, 2012)
A new protocol for the efficient Diels–Alder reaction of 1,2-benzoquinones with arynes is reported. The aryne generated by the fluoride-induced 1,2-elimination of 2-(trimethylsilyl)aryl triflates undergoes a facile Diels–Alder reaction with 1,2-benzoquinones, affording the dioxobenzobicyclooctadienes in moderate to excellent yields. In addition, this methodology has been applied to the one-pot synthesis of benzoquinoxalinobarrelene and naphthalene derivatives.

Efficient synthesis of gamma-keto sulfones by NHC-catalyzed intermolecular stetter reaction - Bhunia, Anup; Yetra, Santhivardhana Reddy; Bhojgude, Sachin Suresh; Biju, Akkattu T. (Organic Letters, 2012)
The N-heterocyclic carbene-catalyzed intermolecular Stetter reaction of aldehydes with α,β-unsaturated sulfones allows the atom-economic and selective formation of γ-keto sulfones in good yields. Key to the success of this unique transition-metal-free carbon–carbon bond-forming reaction is the right choice of the NHC precursor and base. The reaction tolerates a broad range of different aldehydes.

Practical and general diels-alder reaction of pentafulvenes with arynes - Bhojgude, Sachin Suresh; Kaicharla, Trinadh; Bhunia, Anup; Biju, Akkattu T. (Organic Letters, 2012)
A high-yielding, versatile and practical Diels–Alder reaction of pentafulvenes with arynes under mild reaction conditions is reported. The aryne generated by the fluoride induced 1,2-elimination of 2-(trimethylsilyl)aryl triflates undergoes efficient cycloaddition with 6-substituted and 6,6-disubstituted pentafulvenes leading to the formation of benzonorbornadiene derivatives.

Recent advances in transition-metal-free carbon-carbon and carbon-heteroatom bond-forming reactions using arynes - Bhunia, Anup; Yetra, Santhivardhana Reddy; Biju, Akkattu T. (Chemical Society Reviews, 2012)
This tutorial review is aimed at highlighting recent developments in transition-metal-free carbon-carbon and carbon-heteroatom bond-forming reactions utilizing a versatile class of reactive intermediates, viz., arynes, which hold the potential for numerous applications in organic synthesis. Key to the success of the resurgence of interest in the rich chemistry of arynes is primarily the mild condition for their generation by the fluoride-induced 1,2-elimination of 2-(trimethylsilyl)aryl triflates. Consequently, arynes have been employed for the construction of multisubstituted arenes with structural diversity and complexity. The versatile transition-metal-free applications of arynes include cycloaddition reactions, insertion reactions and multicomponent reactions. In addition, arynes have found applications in natural product synthesis. Herein, we present a concise account of the major developments that occurred in this field during the past eight years.

Asymmetric N-heterocyclic carbene (NHC)-catalyzed annulation of modified enals with enolizable aldehydes - Yetra, Santhivardhana Reddy; Kaicharla, Trinadh; Kunte, Sunita S.; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2013)
N-Heterocyclic carbene (NHC)-catalyzed highly enantioselective lactonization of modified enals with enolizable aldehydes, proceeding via the alpha,beta-unsaturated acylazolium intermediates, is reported. The reaction results in the asymmetric synthesis of synthetically important 4,5-disubstituted dihydropyranones.

Employing arynes in transition-metal-free monoarylation of aromatic tertiary amines - Bhojgude, Sachin Suresh; Kaicharla, Trinadh; Biju, Akkattu T. (Organic Letters, 2013)
The highly monoselective N-arylation of aromatic tertiary amines using a transition-metal-free approach using arynes has been developed. The reaction afforded functionalized diaryl amines in moderate to excellent yield. High levels of functional group compatibility especially with halogen containing substrates, dyes and donor-acceptor systems, and high yields of products are the notable features of the present reaction.

Engaging isatins in solvent-free, sterically congested passerini reaction - Kaicharla, Trinadh; Yetra, Santhivardhana Reddy; Roy, Tony; Biju, Akkattu T. (Green Chemistry, 2013)
A facile, atom-economic and environmentally-benign protocol for the synthesis of biologically important oxindole derivatives in high yields has been demonstrated by employing isatins as carbonyl compound surrogates in a Passerini reaction carried out under solvent-free conditions. Moreover, electron-deficient phenols can also be used as the acid component in this reaction. In addition, the synthetic utility of the present methodology was examined by the one-pot synthesis of oxindoles with a free -OH group at the benzylic position.

Multicomponent reactions involving arynes, quinolines, and aldehydes - Bhunia, Anup; Porwal, Digvijay; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2013)
The multicomponent reaction involving arynes, quinolines, and aldehydes leading to the diastereoselective synthesis of benzoxazino quinoline derivatives in good yields proceeding via 1,4-zwitterionic intermediates is reported. In addition, the synthetic potential of various carbonyl compounds in this reaction as well as the utility of isoquinoline as the nucleophilic trigger has been examined.

NHC-Catalyzed reaction of enals with hydroxy chalcones: diastereoselective synthesis of functionalized coumarins - Bhunia, Anup; Patra, Atanu; Puranik, Vedavati G.; Biju, Akkattu T. (Organic Letters, 2013)
The N-heterocyclic carbene-catalyzed annulation of enals with 2'-hydroxy chalcones afford cyclopentane-fused coumarin derivatives with an excellent level of diastereocontrol. The reaction tolerates a broad range of functional groups; 25 examples are given, and a preliminary mechanistic investigation is provided.

Transition-metal-free multicomponent reactions involving arynes, N-heterocycles, and isatins - Bhunia, Anup; Roy, Tony; Pachfule, Pradip; Rajamohanan, Pattuparambil R.; Biju, Akkattu T. (Angewandte Chemie-International Edition, 2013)
Mix and match: With isoquinoline as the nucleophilic trigger, multicomponent reactions afforded spirooxazino isoquinoline derivatives, proceeding through 1,4-dipolar intermediates. The use of pyridine as a nucleophile furnished indolin-2-one derivatives, with the reaction likely proceeding through a pyridylidene intermediate.

Diels-alder reaction of tropones with arynes: synthesis of functionalized benzobicyclo[3.2.2]nonatrienones - Thangaraj, Manikandan; Bhojgude, Sachin Suresh; Bisht, Rajesh H.; Gonnade, Rajesh G.; Biju, Akkattu T. (Journal of Organic Chemistry, 2014)
A new procedure for the mild, practical, and scalable Diels–Alder reaction of tropones with arynes is reported. Differently substituted tropones undergo selective [4 + 2] cycloaddition with arynes generated in situ by the fluoride-induced 1,2-elimination of 2-(trimethylsilyl)aryl triflates, allowing the formation of functionalized benzobicyclo[3.2.2]nonatrienone derivatives in moderate to good yields. In addition, the photophysical properties of the cycloadducts are presented.

Efficient synthesis of 9-aryldihydrophenanthrenes by a cascade reaction involving arynes and styrenes - Bhojgude, Sachin Suresh; Bhunia, Anup; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2014)
A mild, general, and transition-metal-free protocol for the synthesis of 9,10-dihydrophenanthrenes is reported. The aryne generated by the fluoride-induced,1,2-elimination of 2-(trimethylsilyl)aryl triflates undergoes an efficient cascade reaction initiated by the Diels-Alder reaction with the differently substituted styrenes leading to the formation of 9-aryl-9,10-dihydrophenanthrene derivatives in moderate to good yields.

Employing arynes in transition-metal-free, N-heterocycles initiated multicomponent reactions - Bhunia, Anup; Biju, Akkattu T. (Synlett, 2014)
Transition-metal-free multicomponent reactions involving arynes, N-heterocycles, and various carbonyl compounds have been reported. With (iso)quinoline as the nucleophile and carbonyl compounds, such as aldehydes, ketones, and N-substituted isatins as electrophiles, the reaction afforded oxazino (iso)quinoline derivatives and the reaction proceeded via 1,4-dipolar intermediates. Interestingly, when the nucleophilic trigger used is pyridine, the reaction furnished indolin-2-one derivatives, and it is probable that the reaction proceeds via a pyridylidene intermediate.
Keywords: arynes - multicomponent reaction - oxindoles - pyridines - quinolines

Facile synthesis of gamma-ketophosphonates by an intermolecular stetter reaction onto vinylphosphonates - Patra, Atanu; Bhunia, Anup; Biju, Akkattu T. (Organic Letters, 2014)
The atom-economic and practical N-heterocyclic carbene (NHC) catalyzed Stetter reaction for the synthesis of gamma-ketophosphonates by the reaction of aromatic aldehydes with vinylphosphonates is reported. The NHC derived from N-mesitylimidazolium salt (IMes) was an effective catalyst for this transformation, and the products were formed in moderate to good yields.

Multicomponent reactions involving phosphines, arynes and aldehydes - Bhunia, Anup; Kaicharla, Trinadh; Porwal, Digvijay; Gonnade, Rajesh G.; Biju, Akkattu T. (Chemical Communications, 2014)
Although nucleophilic phosphine-catalysis is a powerful tool for the construction of various carbocycles and heterocycles, the reactions in which phosphines are incorporated into the final product are rare, and the reports on phosphine addition to highly electrophilic arynes are scarce. Herein, we report the phosphine triggered multicomponent reaction of arynes and aldehydes, which takes place via the formal [3+2] cycloaddition of an initially generated 1,3-phosphonium zwitterion from phosphines and arynes with aldehydes. The reaction resulted in the formation of a diverse range of stable pentacovalent phosphoranes in good yields based on the benzooxaphosphole system.

N-Heterocyclic carbene-catalyzed enantioselective synthesis of functionalized cyclopentenes via alpha,beta-unsaturated acyl azoliums - Mondal, Santigopal; Yetra, Santhivardhana Reddy; Patra, Atanu; Kunte, Sunita S.; Gonnade, Rajesh G.; Biju, Akkattu T. (Chemical Communications, 2014)
Highly enantioselective NHC-organocatalyzed synthesis of functionalized cyclopentenes proceeding via alpha,beta-unsaturated acyl azolium intermediates is reported. The organocascade reaction of modified enals with malonic ester derivatives having a gamma-benzoyl group involves the Michael-intramolecular aldol-beta-lactonization-decarboxylation sequence to deliver cyclopentenes in good yields and excellent ee values.

Practical synthesis of phthalimides and benzamides by a multicomponent reaction involving arynes, isocyanides, and CO2/H2O - Kaicharla, Trinadh; Thangaraj, Manikandan; Biju, Akkattu T. (Organic Letters, 2014)
Transition-metal-free multicomponent reactions involving arynes and isocyanides with either CO2 or H2O have been reported. With CO2 as the third component, the reactions resulted in the formation of N-substituted phthalimides. The utility of water as the third component furnished benzamide derivatives in moderate to good yields. These reactions took place under mild conditions with broad scope.

Rapid access to benzoxaphospholes and their spiro analogues by a three-component coupling involving arynes, phosphines, and activated ketones - Bhunia, Anup; Roy, Tony; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2014)
An operationally simple multicomponent coupling involving in situ generated arynes from 2 (trimethylsilyl)aryl triflates, phosphines, and various acyclic and cyclic activated carbonyl compounds has been developed. The reaction proceeds via a formal [3 + 2] cycloaddition mode giving access to differently substituted (spiro)benzoxaphosphole derivatives in moderate to good yields Mild reaction conditions. a broad scope. and the possibility of varying all the three-components are the notable features of the present reaction.

Synthesis of functionalized coumarins and quinolinones by NHC-catalyzed annulation of modified enals with heterocyclic C-H acids - Yetra, Santhivardhana Reddy; Roy, Tony; Bhunia, Anup; Porwal, Digvijay; Biju, Akkattu T. (Journal of Organic Chemistry, 2014)
N-Heterocyclic carbene (NHC) catalyzed lactonization and lactamization of 2-bromoenals with heterocyclic C–H acids proceeding via the α,β-unsaturated acyl azolium intermediates is reported. The reaction furnished coumarin- or quinolinone-fused lactone/lactam derivatives. In addition, results of the enantioselective version of this reaction using chiral NHC are presented.

Tandem [4 + 2]/[2 + 2] cycloaddition reactions involving indene or benzofurans and arynes - Bhojgude, Sachin Suresh; Thangaraj, Manikandan; Suresh, Eringathodi; Biju, Akkattu T. (Organic Letters, 2014)
The reaction of arynes with indene/benzofurans has been developed. The arynes were generated from 2-(trimethylsilyl)aryl triflates by the fluoride-induced 1,2-elimination react with indene or various benzofurans proceeding via a cascade reaction involving the Diels–Alder reaction and a [2 + 2] cycloaddition reaction. The tandem process afforded functionalized dihydrobenzocyclobutaphenanthrenes in moderate to good yields. Moreover, the method has been utilized for the one-pot synthesis of benzo[b]fluoranthene.

Diastereoselective synthesis of cyclopentanone-fused spirooxindoles by N-heterocyclic carbene-catalyzed homoenolate annulation with isatilidenes - Patra, Atanu; Bhunia, Anup; Yetra, Santhivardhana Reddy; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Chemistry Frontiers, 2015)
N-Heterocyclic carbene (NHC)-catalyzed formal [3 + 2] annulation of α,β-unsaturated aldehydes with N-substituted isatilidenes resulting in the diastereoselective synthesis of cyclopentanone-fused spirooxindoles is demonstrated. Mechanistically, the reaction proceeds via the generation of homoenolate equivalent intermediates from NHC and enals, which on interception with isatilidenes afford spiroheterocyclic compounds bearing an all-carbon quaternary spiro-center in moderate to good yields and generally with high diastereoselectivity. Moreover, the functionalization of the spirooxindoles as well as the initial studies on the enantioselective version of this reaction are presented.

Enantioselective synthesis of functionalized pyrazoles by NHC-catalyzed reaction of pyrazolones with alpha,beta-unsaturated aldehydes - Yetra, Santhivardhana Reddy; Mondal, Santigopal; Suresh, Eringathodi; Biju, Akkattu T. (Organic Letters, 2015)
The N-heterocyclic carbene (NHC)-organocatalyzed enantioselective annulation reaction of pyrazolones with alpha,beta-unsaturated aldehydes proceeding via the chiral alpha,beta-unsaturated acyl azolium intermediates under oxidative conditions is presented. The reaction afforded dihydropyranone-fused pyrazoles in moderate to good yields and good er values under operationally simple and base-free conditions.

N-Heterocyclic carbene-catalyzed diastereoselective synthesis of β-lactone-fused cyclopentanes using homoenolate annulation reaction - Mukherjee, Subrata; Mondal, Santigopal; Patra, Atanu; Gonnade, Rajesh G.; Biju, Akkattu T. (Chemical Communications, 2015)
NHC-catalyzed annulation of enals with 2-enoylpyridines or 2-enoylpyridine N-oxides leading to the diastereoselective synthesis of β-lactone-fused cyclopentanes is reported. The reaction proceeds via the generation of homoenolate equivalent intermediates and tolerates a broad range of functional groups.

Reaction of N-heterocyclic carbenes with chalcones leading to the synthesis of deoxy-breslow intermediates in their oxidized form - Bhunia, Anup; Thorat, Shridhar H.; Gonnade, Rajesh G.; Biju, Akkattu T. (Chemical Communications, 2015)
The synthesis of deoxy-Breslow intermediates in their oxidized form has been developed via the reaction of N-heterocyclic carbenes (NHCs) with chalcones. Moreover, the initial tetrahedral adduct formed from the 1,4-addition of NHCs to chalcones is also isolated.

Recent advances in employing homoenolates generated by N-heterocyclic carbene (NHC) catalysis in carbon-carbon bond-forming reactions - Menon, Rajeev S.; Biju, Akkattu T.; Nair, Vijay (Chemical Society Reviews, 2015)
The use of NHCs for generating homoenolate species has gained widespread popularity in recent years. A number of highly stereoselective processes of NHC-homoenolates have emerged. Homoenolate reactions have also been employed as key steps in the total synthesis of a number of natural products. The use of compatible co-catalysts, improved NHC-catalyst design and the use of novel precursors for homoenolate generation are among the major developments in this area that were disclosed recently. This tutorial review organises and presents the advancements in this rapidly growing area of catalysis and in the process updates a previous account published in 2011 in this journal.

Recent advances in the N-heterocyclic carbene (NHC)-organocatalyzed stetter reaction and related chemistry - Yetra, Santhivardhana Reddy; Patra, Atanu; Biju, Akkattu T. (Synthesis‐Stuttgart, 2015)
Recent developments in the N-heterocyclic carbene (NHC)-catalyzed umpolung of aldehydes followed by their interception with activated carbon–carbon double bonds, namely the Stetter reaction, are presented. Advances in the inter- and intramolecular versions of this reaction, enantioselective transformations as well as the use of unactivated olefins in this type of reaction are discussed.

Synthesis of N-aryl beta-amino alcohols by trifluoroacetic acid promoted multicomponent coupling of aziridines, arynes, and water - Roy, Tony; Baviskar, Dnyaneshwar R.; Biju, Akkattu T. (Journal of Organic Chemistry, 2015)
A transition-metal-free, three-component coupling involving N-substituted aziridines, arynes, and water promoted by trifluoroacetic acid (TFA) has been reported. The reaction furnished medicinally important N-aryl beta-amino alcohol derivatives in moderate to good yields. In addition, the use of azetidines in this reaction afforded N-aryl gamma-amino alcohol derivatives.

Three-component coupling involving arynes, aromatic tertiary amines, and aldehydes via aryl-aryl amino group migration - Bhojgude, Sachin Suresh; Baviskar, Dnyaneshwar R.; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2015)
The transition-Metal-free multicomponent coupling of arynes, aromatic tertiary amines, and aldehydes proceeding via the aryl to aryl amino group migration has been demonstrated. This protocol allows rapid access to ortho-functionalized tertiary amines in moderate to good yields. Moreover, activated ketones can also be used as the aldehyde Component in the present reaction. The similarity of the aryl-aryl tertiary amino group migration with the Smiles rearrangement is striking.

Aryne [2,3] stevens rearrangement - Roy, Tony; Thangaraj, Manikandan; Kaicharla, Trinadh; Kamath, Rupa V.; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2016)
Arynes are employed in the transition-metal-free and mild [2,3] Stevens rearrangement of tertiary allylic amines for the synthesis of functionalized homoallylic amines in moderate to good yield with a broad substrate scope. The key nitrogen ylide intermediate was generated by the N-arylation of allyl amines using arynes. Moreover, the reaction of chiral allyl amines with arynes resulted in the enantiospecific synthesis of homoallylic amines. In addition, preliminary studies on the [1,2] Stevens rearrangement is also presented.

Employing arynes in diels–alder reactions and transition-metal-free multicomponent coupling and arylation reactions - Bhojgude, Sachin Suresh; Bhunia, Anup; Biju, Akkattu T. (Accounts of Chemical Research, 2016)
Conspectus <p class="articleBody_abstractText" style="margin: 0px 0px 1.5em; line-height: 1.6em; padding: 0pt; width: 610px; word-wrap: break-word; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;">Arynes are highly reactive intermediates having several applications in organic synthesis for the construction of various ortho-disubstituted arenes. Traditionally, arynes are generated in solution from haloarenes under strongly basic conditions. However, the scopes of many of the aryne reactions are limited because of the harsh conditions used for their generation. The renaissance of interest in aryne chemistry is mainly due to the mild conditions for their generation by the fluoride-induced 1,2-elimination of 2-(trimethylsilyl)aryl triflates. This Account is focused on the Diels–Alder reaction of arynes and their transition-metal-free application in multicomponent couplings as well as arylation reactions. <p class="articleBody_abstractText" style="margin: 0px 0px 1.5em; line-height: 1.6em; padding: 0pt; width: 610px; word-wrap: break-word; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;">The Diels–Alder reaction of arynes is a powerful tool for constructing benzo-fused carbocycles and heterocycles. In 2012, we developed an efficient, broad-scope, and scalable Diels–Alder reaction of pentafulvenes with arynes affording benzonorbornadiene derivatives. Subsequently, we accomplished the Diels–Alder reaction of arynes with dienes such as 1,2-benzoquinones and tropones. Moreover, we uncovered a transition-metal-free protocol for the synthesis of 9,10-dihydrophenanthrenes by the reaction of arynes with styrenes that proceeds via a Diels–Alder/ene-reaction cascade. In addition, we demonstrated the reaction of arynes with indene/benzofurans, which proceeds via a tandem [4 + 2]/[2 + 2] sequence. <p class="articleBody_abstractText" style="margin: 0px 0px 1.5em; line-height: 1.6em; padding: 0pt; width: 610px; word-wrap: break-word; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;">Multicomponent coupling (MCC) involving arynes mainly comprises the initial addition of a nucleophile to the aryne followed by interception of the aryl anion intermediate with an electrophile (provided the nucleophilic and electrophilic moieties do not belong to the same molecule). We have disclosed aryne MCCs initiated by N-heterocycles such as (iso)quinoline, pyridine, and aziridines. When (iso)quinoline is used as the nucleophilic trigger and N-substituted isatin as the third component, the reaction affords spirooxazino(iso)quinolines via 1,4-dipolar intermediates. Unexpectedly, using pyridine affords indolin-2-ones, where the reaction proceeds via the pyridylidene intermediate. Additionally, we developed the phosphine-triggered aryne MCCs for the synthesis of functionalized benzooxaphospholes. In another phase of our work, we studied the synthetic utility of CO2 as a one-carbon synthon in aryne MCCs for the synthesis of phthalimides. <p class="articleBody_abstractText" style="margin: 0px 0px 1.5em; line-height: 1.6em; padding: 0pt; width: 610px; word-wrap: break-word; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;">Engaging arynes as an aryl source is one of the transition-metal-free methods for arylation reactions. We have demonstrated the N-arylation of aromatic tertiary amines and O-arylation of aliphatic alcohols using arynes. <p class="articleBody_abstractText" style="margin: 0px 0px 1.5em; line-height: 1.6em; padding: 0pt; width: 610px; word-wrap: break-word; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;">It is anticipated that the chemistry of arynes will continue to prosper and will lead to surprising developments for the synthesis of various 1,2-disubstituted arenes of molecular complexity and structural diversity. Future challenges in this area include the utility of arynes in enantioselective transformations and the synthesis and reactions of exotic heterocyclic arynes.
Keywords: 2-Benzoquinones; Cycloaddition; Facile N-arylation; O-arylation; One-Pot; Aldehydes; Benzyne; Amines; Heterocycles; Acids; 1

Employing carboxylic acids in aryne multicomponent coupling triggered by aziridines/azetidines - Roy, Tony; Bhojgude, Sachin Suresh; Kaicharla, Trinadh; Thangaraj, Manikandan; Garai, Bikash; Biju, Akkattu T. (Organic Chemistry Frontiers, 2016)
The transition-metal-free aryne multicomponent coupling (MCC) involving carboxylic acids initiated by aziridines/azetidines has been reported. The use of aziridines as nucleophiles afforded N-aryl beta-amino alcohol derivatives and the application of azetidines as nucleophilic triggers furnished N-aryl gamma-amino alcohol derivatives in moderate to good yields. These reactions proceed under mild conditions and result in the formation of a new carbon-nitrogen bond and a new carbon-oxygen bond. The utility of carboxylic acids in aryne MCCs has been demonstrated, and the synthetic potential of phenols as acid surrogates in the present aryne MCCs has been realized.

Enantioselective synthesis of spirocyclohexadienones by NHC-catalyzed formal [3+3] annulation reaction of enals - Yetra, Santhivardhana Reddy; Mondal, Santigopal; Mukherjee, Subrata; Gonnade, Rajesh G.; Biju, Akkattu T. (Angewandte Chemie-International Edition, 2016)
The enantioselective synthesis of pyrazolone-fused spirocyclohexadienones was demonstrated by the reaction of alpha,beta-unsaturated aldehydes with alpha-arylidene pyrazolinones under oxidative N-heterocyclic carbene (NHC) catalysis. This atom-economic and formal [3+3] annulation reaction proceeds through a vinylogous Michael addition/spiroannulation/dehydrogenation cascade to afford spirocyclic compounds with an all-carbon quaternary stereocenter in moderate to good yields and excellent ee values. Key to the success of the reaction is the cooperative NHC-catalyzed generation of chiral alpha,beta-unsaturated acyl azoliums from enals, and base-mediated tandem generation of dienolate/enolate intermediates from pyrazolinones.
Keywords: annulation reactions; asymmetric catalysis; N-heterocyclic carbenes; organocatalysis; spiro compounds

From insertion to multicomponent coupling: temperature dependent reactions of arynes with aliphatic alcohols - Thangaraj, Manikandan; Bhojgude, Sachin Suresh; Mane, Manoj V.; Biju, Akkattu T. (Chemical Communications, 2016)
The temperature dependent selectivity switch in the reaction of arynes with aliphatic alcohols in THF has been reported. At -20 degrees C, arynes smoothly insert into the O-H bond of alcohols to form alkyl aryl ethers. Interestingly, at 60 degrees C, a highly selective multicomponent coupling occurs with the solvent THF acting as the nucleophilic trigger affording (4-(alkoxy)butoxy)arenes.

Lewis acid catalyzed selective reactions of donor-acceptor cyclopropanes with 2-naphthols - Kaicharla, Trinadh; Roy, Tony; Thangaraj, Manikandan; Gonnade, Rajesh G.; Biju, Akkattu T. (Angewandte Chemie-International Edition, 2016)
Lewis acid-catalyzed reactions of 2-substituted cyclopropane 1,1-dicarboxylates with 2-naphthols is reported. The reaction exhibits tunable selectivity depending on the nature of Lewis acid employed and proceed as a dearomatization/rearomatization sequence. With Bi(OTf)(3) as the Lewis acid, a highly selective dehydrative [3+2] cyclopentannulation takes place leading to the formation of naphthalene-fused cyclopentanes. Interestingly, engaging Sc(OTf)(3) as the Lewis acid, a Friedel-Crafts-type addition of 2-naphthols to cyclo-propanes takes place, thus affording functionalized 2-naphthols. Both reactions furnished the target products in high regioselectivity and moderate to high yields.
Keywords: annulations; arenes; Lewis acids; reaction mechanisms; small ring systems

Recent advances in N-heterocyclic carbene (NHC)-catalysed benzoin reactions - Menon, Rajeev S.; Biju, Akkattu T.; Nair, Vijay (Beilstein Journal of Organic Chemistry, 2016)
N-Heterocyclic carbenes (NHCs) have emerged as a powerful class of organocatalysts that mediate a variety of organic transformations. The Benzoin reaction constitutes one of the earliest known carbon-carbon bond-forming reactions catalysed by NHCs. The rapid growth of NHC catalysis in general has resulted in the development of a variety of benzoin and benzoin-type reactions. An overview of such NHC-catalysed benzoin reactions is presented.
Keywords: acyloin reaction; benzoin reaction; N-heterocyclic carbenes; organocatalysis; umpolung

Recent advances in N-heterocyclic carbene (NHC)-catalysed benzoin reactions (vol 12, pg 444, 2016) - Menon, Rajeev S.; Biju, Akkattu T.; Nair, Vijay (Beilstein Journal of Organic Chemistry, 2016)
Keywords: acyloin reaction; benzoin reaction; N-heterocyclic carbenes; organocatalysis; umpolung

Selective synthesis of N-unsubstituted and N-arylindoles by the reaction of arynes with azirines - Thangaraj, Manikandan; Bhojgude, Sachin Suresh; "Jain, Shailja"; Gonnade, Rajesh G.; Biju, Akkattu T. (Journal of Organic Chemistry, 2016)
The transition-metal-free and temperature-dependent highly selective reaction of arynes with 2H-azirines allowing the synthesis of either N-unsubstituted or N-arylindoles has been developed. At 60 degrees C, arynes generated from 2-(trimethylsilyl)aryl triflates smoothly insert into 2H-azirines to form 2,3-diarylindoles with high selectivity. Interestingly, when the reaction was performed at -10 degrees C, the selectivity was switched to the formation of 1,2,3-triarylindoles in good yields.

Substrate-controlled selectivity switch in the three-component coupling involving arynes, aromatic tertiary amines, and CO2 - Bhojgude, Sachin Suresh; Roy, Tony; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2016)
The transition-metal-free multicomponent coupling involving arynes, aromatic tertiary amines, and CO2 is reported. The reaction exhibits switchable selectivity depending on the electronic nature of the aromatic amines used. With amines bearing electron-releasing/neutral groups as the nucleophilic trigger, the reaction afforded 2-arylamino benzoates via a nitrogen to oxygen alkyl group migration. Employing electron-deficient amines in the reaction furnished 2-aminoaryl benzoates proceeding via the aryl to aryl amino group migration resembling a Smiles rearrangement.

Synthesis of 4H-chromenes by an unexpected, K3PO4-mediated intramolecular rauhut–currier type reaction - Bhunia, Anup; Yetra, Santhivardhana Reddy; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic & Biomolecular Chemistry, 2016)
In an attempt to develop the umpolung of Michael acceptors using chalcones having an enoate moiety under N-heterocyclic carbene (NHC) catalysis, a K3PO4-mediated intramolecular Rauhut–Currier type reaction was observed. This C(sp2)–C(sp2) coupling reaction afforded the biologically important 4H-chromenes in moderate to good yields. It is likely that the enol ether functionality acts as the nucleophilic trigger in this reaction.

Synthesis of functionalized amino epoxides by a three-component coupling involving aziridines, arynes and aldehydes - Roy, Tony; Thangaraj, Manikandan; Gonnade, Rajesh G.; Biju, Akkattu T. (Chemical Communications, 2016)
A transition-metal-free three-component coupling involving N-substituted aziridines, arynes and aldehydes resulting in the formation of trisubstituted N-aryl alpha-amino epoxides has been demonstrated. The reaction likely proceeds via the highly strained cyclic nitrogen ylide intermediates generated from aziridines and arynes.

AgOTf-catalyzed dehydrative [3+2] annulation of aziridines with 2-naphthols - Kaicharla, Trinadh; Jacob, Anu; Gonnade, Rajesh G.; Biju, Akkattu T. (Chemical Communications, 2017)
The reaction of 2-naphthols with aziridines in the presence of AgOTf resulting in a dehydrative, formal [3+2] annulation is reported. The reaction allows the synthesis of functionalized benzoindolines, and tolerates a broad range of functional groups. A preliminary study on themechanism of this reaction indicates an SN1-type ring-opening of aziridines. This method is demonstrated for the one-pot synthesis of benzoindoles.

Base-free and catalyst-free synthesis of functionalized dihydrobenzoxazoles via vinylogous carbonate to carbamate rearrangement - Das, Tamal Kanti; Mondal, Santigopal; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2017)
An unexpected, catalyst-free, and base-free intramolecular cyclization of N-aryloxyacrylate aldimines, under thermal conditions leading to the synthesis of functionalized dihydrobenzoxazoles, is reported. The reaction features a unique rearrangement of vinylogous carbonates to vinylogous carbamates resulting in a new carbon–oxygen and carbon–nitrogen bond construction. The reaction tolerates a broad range of functional groups and the desired products are formed in moderate to good yields.

Enantioselective synthesis of functionalized β-lactones by NHC-catalyzed aldol lactonization of ketoacids - Mondal, Santigopal; Mukherjee, Subrata; Das, Tamal Kanti; Gonnade, Rajesh G.; Biju, Akkattu T. (Journal of Organic Chemistry, 2017)
N-Heterocyclic carbene (NHC)-catalyzed intramolecular aldol lactonization of readily available ketoacids leading to the enantioselective synthesis of cyclopentane-fused β-lactones is presented. The reaction proceeds via the generation of NHC-bound enolate intermediates formed from the ketoacids in the presence of the peptide coupling reagent HATU and NHC generated from the chiral triazolium salt. The functionalized β-lactones are formed under mild conditions in high yields and enantioselectivities.

Enantioselective synthesis of spiro γ-butyrolactones by N-heterocyclic carbene (NHC)-catalyzed formal [3+2] annulation of enals with 3-hydroxy oxindoles - Mukherjee, Subrata; Joseph, Sumi; Bhunia, Anup; Gonnade, Rajesh Ghanshyam; Reddy, Santhi Vardhan; Biju, Akkattu T. (Organic & Biomolecular Chemistry, 2017)
The N-heterocyclic carbene (NHC)-catalyzed enantioselective formal [3 + 2] annulation of α,β-unsaturated aldehydes with 3-hydroxy oxindoles is presented. Under oxidative conditions using the bisquinone oxidant, the reaction resulted in the synthesis of spiro γ-butyrolactones in moderate to good yields, enantioselectivity and diastereoselectivity. The reaction likely proceeds via the generation of the NHC-bound α,β-unsaturated acylazolium intermediate from enals, which was intercepted by the dioxindoles in a formal [3 + 2] pathway to form the spirocyclic compounds. However, a deeper mechanistic investigation revealed that the reaction can also proceed via the homoenolate intermediate. In this case, the dioxindole was oxidized to the corresponding isatin derivative using traces of air under basic conditions, and was intercepted with the NHC-bound homoenolate intermediate in a formal [3 + 2] pathway to afford the spiro compound.

Facile synthesis of N-acyl 2-aminobenzothiazoles by NHC-catalyzed direct oxidative amidation of aldehydes - Premaletha, Sethulekshmi; Ghosh, Arghya; Joseph, Sumi; Reddy, Santhi Vardhan; Biju, Akkattu T. (Chemical Communications, 2017)
A mild, general, and high yielding synthesis of N-acyl 2-aminobenzothiazoles has been demonstrated by N-heterocyclic carbene (NHC)-organocatalyzed direct amidation of aldehydes with 2-aminobenzothiazoles proceeding via acyl azolium intermediates. The carbene generated from the triazolium salt under oxidative conditions was the key for the success of this reaction. The method was subsequently applied to the synthesis of various biologically important N-acyl 2-aminobenzothiazoles.

Metal-free, brønsted acid-catalyzed formal [3+2] annulation of quinone monoacetals with 2-naphthols - Jacob, Anu; Roy, Tony; Kaicharla, Trinadh; Biju, Akkattu T. (Journal of Organic Chemistry, 2017)
An operationally simple and metal-free cross-coupling of quinone monoacetals (QMAs) with 2-naphthols catalyzed by triflic acid is reported. This formal [3+2] annulation allowed the synthesis of diverse naphtho[2,1-b]benzofuranderivatives in moderate to good yields. Preliminary mechanistic studies reveal the initial nucleophilic substitution of QMAs with 2-naphthols in preference to the mixed acetal formation and subsequent [3,3] sigmatropic rearrangement.

Method for the analysis of free carbenes present after NHC-organocatalyzed transformations - Das, Tamal Kanti; Biju, Akkattu T. (European Journal of Organic Chemistry, 2017)
In N-heterocyclic carbene (NHC) based organocatalysis, usually, the free carbene is generated in situ by treatment of the azolium salt with a base. Described herein is a method for the analysis of the NHC present in the reaction flask after the NHC-organocatalyzed reaction. For this, the reaction mixture was treated with elemental sulfur after the reaction and the thus-formed thiourea/thione derivative was isolated. Common NHC-catalyzed transformations such as benzoin reactions, Stetter reactions, homoenolate annulation reactions, and reactions proceeding via the ,-unsaturated acylazolium intermediate have been studied. The results indicate that after the reactions, 28-84% of the initial carbenes exist in the free form.

N - heterocyclic - carbene - catalyzed umpolung of imines - Patra, Atanu; Mukherjee, Subrata; Das, Tamal Kanti; Jain, Shailja; Gonnade, Rajesh Ghanshyam; Biju, Akkattu T. (Angewandte Chemie International Edition, 2017)
N-Heterocyclic carbene (NHC) catalysis has been widely used for the umpolung of aldehydes, and recently for the umpolung of Michael acceptors. Described herein is the umpolung of aldimines catalyzed by NHCs, and the reaction likely proceeds via aza-Breslow intermediates. The NHC-catalyzed intramolecular cyclization of aldimines bearing a Michael acceptor resulted in the formation of biologically important 2-(hetero)aryl indole 3-acetic-acid derivatives in moderate to good yields. The carbene generated from the bicyclic triazolium salt was found to be efficient for this transformation.

N-Heterocyclic carbene-catalyzed aldol-lactonization of ketoacids via dynamic kinetic resolution - Mondal, Santigopal; Mukherjee, Subrata; Das, Tamal Kanti; Gonnade, Rajesh; Biju, Akkattu T. (ACS Catalysis, 2017)
N-Heteroryclic carbene (NHC)-catalyzed enantioselective aldol lactonization of acyclic ketoacids, proceeding via dynamic kinetic resolution, is presented. The carbene generated from the chiral anninoinclanol-derived triazolium salt in the presence of LiCl was the key for the success of this transformation. The reaction allowed the diastereoselective and enantioselective synthesis of cyclopentane-fused beta-lactones having three contiguous stereocenters. The reaction products are shown to undergo substrate-controlled beta-lactone opening in the presence of amines to afford succinimide derivatives with four contiguous stereocenters.
Keywords: aldol lactonization; beta-lactones; DKR strategies; ketoacids; N-heterocyclic carbenes; organocatalysis

Organocatalytic enantioselective vinylogous michael-aidoi cascade for the synthesis of spirocyclic compounds - Mondal, Santigopal; Mukherjee, Subrata; Yetra, Santhivardhana Reddy; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2017)
Enantioselective synthesis of pyrazolone-fused spirocyclohexenols by the secondary amine-catalyzed cascade reaction of alpha,beta-unsaturated aldehydes with alpha-arylidene pyrazolinones is reported. This formal [3 + 3] organocascade reaction proceeds through a vinylogous Michael-aldol sequence to furnish the spiroheterocycles with three stereocenters including an all-carbon quaternary center in good yields and selectivities. The catalytic generation of alpha,beta-unsaturated iminium ions from enals and tandem dienolate/enolate formation from pyrazolinones are the key for the success of this spiroannulation reaction.

Synthesis of functionalized β-keto arylthioethers by the aryne induced [2,3] Stevens rearrangement of allylthioethers - Thangaraj, Manikandan; Gaykar, Rahul N.; Roy, Tony; Biju, Akkattu T. (Journal of Organic Chemistry, 2017)
A mild and transition-metal-free synthesis of β-keto arylthioethers has been developed by the aryne triggered [2,3] Stevens rearrangement of allylthioethers. The key sulfur ylide intermediate for the rearrangement was formed by the S-arylation of allylthioethers with arynes generated from 2-(trimethylsilyl)aryl triflates using CsF. Later, the reaction products are converted into valuable heterocycles in two steps.

Employing arynes for the generation of aryl anion equivalents and subsequent reaction with aldehydes - Gaykar, Rahul N.; Bhunia, Anup; Biju, Akkattu T. (Journal of Organic Chemistry, 2018)
Arynes are highly reactive intermediates, which are utilized for the electrophilic arylation of various X-H bonds (X = O, N, S etc.). Herein, a new synthetic strategy is demonstrated, where arynes are converted into aryl anion equivalents by treatment with phosphines and a base. The addition of phosphines to arynes form the phosphonium salts, which in the presence of a carbonate base generates the aryl anion equivalent. Subsequent addition of the aryl anions with aldehydes afforded the secondary alcohols.

Enantioselective N-heterocyclic carbene-catalyzed cascade reaction for the synthesis of pyrroloquinolines via N-H functionalization of indoles - Mukherjee, Subrata; Shee, Sayan; Poisson, Thomas; Besset, Tatiana; Biju, Akkattu T. (Organic letters, 2018)
Functionalization of the indole N-H bond for enantioselective synthesis of biologically important pyrroloquinoline derivatives has been reported under oxidative N-heterocyclic carbene catalysis conditions. The interception of catalytically generated chiral alpha,beta-unsaturated acylazoliums with the indole derivatives proceeds in an aza-Michael/Michael/lactonization sequence to deliver the pyrroloquinoline derivatives in good yields, diastereoselectivities, and enantioselectivities. The simultaneous enhancement of reactivity and selectivity observed in polar aprotic solvents is noteworthy.

N-Heterocyclic carbene-catalyzed enantioselective synthesis of spiro-glutarimides via alpha,beta-unsaturated acylazoliums - Mondal, Santigopal; Ghosh, Arghya; Mukherjee, Subrata; Biju, Akkattu T. (Organic Letters, 2018)
NHC-catalyzed enantioselective [3 + 3] spiro-annulation of alpha,beta-unsaturated aldehydes with cyclic beta-ketoamides allowing the preparation of synthetically and biologically important spiro-glutarimide derivatives has been reported. The interception of the ketoamides with catalytically generated chiral alpha,beta-unsaturated acylazoliums proceeds in a Michael addition-intramolecular amidation pathway to deliver the spirocyclic products with good yield, diastereoselectivity, and enantioselectivity.

N-Heterocyclic carbene-catalyzed michael-michael-lactonization cascade for the enantioselective synthesis of tricyclic delta-lactones - Mukherjee, Subrata; Ghosh, Arghya; Marelli, Udaya Kiran; Biju, Akkattu T. (Organic Letters, 2018)
Enantioselective synthesis of tricyclic delta-lactones with three contiguous stereocenters has been demonstrated by the N-heterocyclic carbene (NHC)-catalyzed functionalization of benzylic C(sp(3))-H bonds. The NHC-catalyzed reaction of enals with dinitrotoluene derivatives under oxidative conditions proceeds via the chiral alpha,beta-unsaturated acylazoliums and produces the delta-lactones in good yields and excellent diastereoselectivity and enantioselectivity. This mild and atom-economic cascade reaction takes place in a Michael/Michael/lactonization sequence and tolerates a broad range of functional groups.

N-Heterocyclic carbene-catalyzed synthesis of alpha-trifluoromethyl esters - Gelat, Fabien; Patra, Atanu; Pannecoucke, Xavier; Biju, Akkattu T.; Poisson, Thomas; Besset, Tatiana (Organic Letters, 2018)
The N-heterocyclic carbene (NHC)-catalyzed trifluoromethylation of alpha-chloro aldehydes was developed, allowing straightforward access to valuable alpha-trifluoromethyl ester derivatives. The unique combination of an electrophilic trifluoromethylation reagent with NHC catalysis was the key for the functionalization of a broad range of alpha-chloro aldehydes, and the products are formed in moderate to good yields. Investigations of the enantioselective version of this reaction afforded the enantioenriched products in moderate yields with good ee values.

Oxidative NHC catalysis for the generation of imidoyl azoliums: synthesis of benzoxazoles - Patra, Atanu; James, Anjima; Das, Tamal Kanti; Biju, Akkattu T. (Journal of Organic Chemistry, 2018)
N-Fleterocyclic carbene (NHC)-catalyzed intramolecular cyclization of aldimines generated from 2-amino phenols and aromatic aldehydes leading to the synthesis of 2-arylbenzoxazoles under mild conditions is presented. The reaction proceeds via the generation of the aza-Breslow intermediates from imines and NHC, which under oxidative conditions form the key imidoyl azoliums and a subsequent intramolecular cyclization furnishes the product. The reaction tolerates a broad range of functional groups, and the products are formed in generally good yields.

Recent advances in molecular rearrangements involving aryne intermediates - Roy, Tony; Biju, Akkattu T. (Chemical Communications, 2018)
This Feature Article is aimed at highlighting the recent developments in the transition-metal-free molecular rearrangements involving arynes. The chemistry of arynes has shown incredible developments especially in transition-metal-free carbon-carbon and carbon-heteroatom bond-forming reactions in the last three decades. The rapid growth in this field is mainly due to the development of mild methods for the generation of arynes. One aspect of the recent developments in the chemistry of arynes involves the molecular rearrangements proceeding via this electrophilic intermediate. The molecular rearrangements have provided direct access to a library of valuable molecules, which cannot be accessed in a single step through other synthetic routes. Herein, we present a concise account on the developments that occurred in this field over the last three decades.

Recent advances in the organocatalytic enantioselective synthesis of functionalized -lactones - Mukherjee, Subrata; Biju, Akkattu T. (Chemistry-An Asian Journal, 2018)
This Focus Review highlights recent developments in the organocatalytic enantioselective synthesis of -lactone derivatives. Owing to the importance of -lactones as a heterocyclic motif that is present in a variety of natural products and biologically active molecules, several catalytic methods have been developed for the synthesis of these compounds in their enantiomerically pure form. Organocatalytic methods that employ N-heterocyclic carbenes (NHCs), cinchona alkaloids, isothioureas, 4-dimethylaminopyridine (DMAP) derivatives, and phosphines have allowed the highly enantioselective synthesis of -lactones from cheap and readily available starting materials. Moreover, the inherent strain in the four-membered ring of -lactones has also been utilized in further synthetic transformations, thus making -lactones a versatile intermediate in organic synthesis.

Synthesis of 4-difluoromethylquinolines by NHC-catalyzed umpolung of imines - Patra, Atanu (Organic Letters, 2018)
The N-heterocyclic carbene (NHC)-catalyzed umpolung of aldimines for the synthesis of 4-difluoromethylquinoline derivatives is reported. In the presence of NHCs, the intramolecular cyclization of aldimines bearing a moderately electron-poor double bond due to the presence of the −CF3 group likely proceeds via the intermediacy of the aza-Breslow intermediate. The key to the success of this aza-Stetter type transformation is the NHC generated from the bicyclic triazolium salt using DBU as the base.

[8+3]-cycloaddition of tropones with azaoxyallyl cations - Roy, Tony; Jacob, Anu; Bhattacharjee, Subrata; Biju, Akkattu T. (Chemistry-An Asian Journal, 2019)
Although azaoxyallyl cations are widely used as 1,3-dipoles for various cycloaddition reactions leading to nitrogen-containing heterocycles, their application in higher-order cycloaddition reaction remains scarce. Herein, we present the [8+3]-cycloaddition reaction of tropones with in situ generated azaoxyallyl cations allowing the one-step construction of cycloheptatriene-fused 1,4-oxazinones in moderate to good yields. This base-promoted new carbon-oxygen and carbon-nitrogen bond-forming reaction takes place under mild conditions in the absence of transition metal catalysts.
Keywords: 1; 4-oxazinones; azaoxyallyl cations; heterocycles; tropones; [8+3] cycloaddition

Aryne Sommelet-Hauser rearrangement - Roy, Tony; Gaykar, Rahul N.; Bhattacharjee, Subrata; Biju, Akkattu T. (Chemical Communications, 2019)
An aryne induced transition-metal-free and mild Sommelet-Hauser rearrangement of tertiary benzylamines for the synthesis of -aryl amino acid derivatives in moderate to good yields is presented. Unlike the conventional Sommelet-Hauser rearrangement of ammonium salts, the methodology developed herein requires neither harsh conditions nor strong bases. Moreover, a temperature dependent switchable selectivity for the Sommelet-Hauser and Stevens [1,2] rearrangements has been observed.

N-heterocyclic carbene-catalyzed stetter reaction and related chemistry - Mondal, Santigopal; Yetra, Santhivardhana R.; Biju, Akkattu T. (N‐Heterocyclic Carbenes in Organocatalysis, 2019)
The reversal of normal mode of reactivity (umpolung) of aldehydes is the most important application of N-heterocyclic carbenes (NHCs) in organocatalytic transformations. The benzoin condensation and the Stetter reaction are the two historic reactions where NHC reacts with aldehyde to generate acyl anion equivalent, which is subsequently intercepted with another molecule of carbonyl compound or Michael acceptor leading to the formation of the benzoin/Stetter products. The objective of this chapter is to provide an overview on NHC-catalyzed Stetter reaction and related chemistry. The development of various chiral catalysts for enantioselective intra- or intermolecular Stetter reaction has been described. Additionally, recent progress on NHC-catalyzed addition of aldehyde to unactivated multiple bonds in the hydroacylation reaction has been demonstrated.

N-Heterocyclic carbene-catalyzed umpolung of imines for the enantioselective synthesis of dihydroquinoxalines - Das, Tamal Kanti; Ghosh, Avik; Balanna, Kuruva; Behera, Pradipta; Gonnade, Rajesh G.; Marelli, Udaya Kiran; Das, Abhijit Kumar; Biju, Akkattu T. (ACS Catalysis, 2019)
N-heterocyclic carbene (NHC) organocatalysis is widely employed for the umpolung of aldehydes and recently to the umpolung of Michael acceptors and aldimines. Described herein is the NHC-organocatalyzed umpolung of aldimines for the enantioselective synthesis of nitrogen heterocycles. The bisimines generated from the condensation of 1,2-phenylenediamines and salicylaldehydes undergo intramolecular cyclization in the presence of a chiral NHC catalyst, resulting in the formation of dihydroquinoxalines in moderate to good yields and er values. Detailed DFT studies shed light on the role of -OH groups in stabilizing the initially generated aza-Breslow intermediates via intramolecular hydrogen bonds. Preliminary photophysical studies on the synthesized dihydroquinoxalines revealed that these molecules can be used for the sensing of various acids and bases.
Keywords: dihydroquinoxalines; imines; N-heterocyclic carbenes; organocatalysis; umpolung

Synthesis of 2-Aryl naphthoquinones by the cross-dehydrogenative coupling involving an NHC-catalyzed endo-stetter reaction - Ghosh, Arghya; Patra, Atanu; Mukherjee, Subrata; Biju, Akkattu T. (Journal of Organic Chemistry, 2019)
An N-heterocyclic carbene (NHC)-catalyzed intramolecular Stetter reaction proceeding via the endo-fashion was the key step for the transition-metal-free and mild cross-dehydrogenative coupling of 2-cinnamoyl benzal-dehydes allowing for the synthesis of 2-aryl naphthoquinones. In this transformation, the carbene generated from the triazolium salt using Na2CO3 catalyzes the intramolecular Stetter reaction, which was followed by air oxidation to reinstall the C-C double bond.

Enantioselective synthesis of tricyclic beta-lactones by NHC-catalyzed desymmetrization of cyclic 1,3-diketones - Shee, Sayan; Mukherjee, Subrata; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2020)
The NHC-catalyzed desymmetrization of cyclic-1,3-diketones allowing the enantioselective construction of tricyclic beta-lactones with five contiguous stereocenters, including two quaternary stereocenters, has been developed. The mild and operationally simple addition of a-bromoenals to cyclopentane-1,3-diketone derivatives proceeds via the initial formation of chiral alpha,beta-unsaturated acylazolium intermediates and culminates in a cascade reaction, following the Michael-aldol-Iactonization pathway to deliver the beta-lactone derivatives in moderate to good yields and excellent selectivity.

Imines as acceptors and donors in N-heterocyclic carbene (NHC) organocatalysis - Das, Tamal Kanti; Biju, Akkattu T. (Chemical Communications, 2020)
The synthetic potential of imines as electrophiles or as a source of nucleophilic coupling partner in N-heterocyclic carbene (NHC) catalysis for the synthesis of various nitrogen heterocycles and functionalized amines is highlighted in this Feature Article. Electrophilic imines are suitable candidates for intercepting the NHC-derived acyl anions, homoenolate equivalents, and (di)enolates for the synthesis of alpha-amino ketones and a variety of lactam derivatives. Moreover, enamines generated from imines bearing alpha-hydrogen could be trapped with alpha,beta-unsaturated acylazoliums for the synthesis of functionalized dihydropyridinones. NHCs are also useful for the umpolung of imines for the generation of aza-Breslow intermediates thus leading to the synthesis of indoles, quinolines, dihydroquinoxalinesetc.A concise account of the diverse reactivity of imines in NHC catalysis has been presented.

N-heterocyclic carbene catalysis exploiting oxidative imine umpolung for the generation of imidoyl azoliums - Das, Tamal Kanti; Madica, Krishnaprasad; Krishnan, Jagadeesh; Marelli, Udaya Kiran; Biju, Akkattu T. (Journal of Organic Chemistry, 2020)
Although NHC-catalyzed umpolung of imines are known, the related reactions under oxidative conditions are limited. Described herein is the two-step process involving the initial formation of aldimines from the corresponding aldehydes and 2-amino benzyl alcohols followed by NHC-catalyzed cyclization proceeding via the imidoyl azoliums under oxidative conditions. The reaction allowed the synthesis of trifluoromethylated 3,1-benzoxazines in good yields and broad scope. The role of NHC in the intramolecular cyclization and preliminary mechanistic experiments are also provided.

N-heterocyclic carbene (NHC)-catalyzed transformations for the synthesis of heterocycles - Das, Tamal Kanti; Biju, Akkattu T. (Progress in Heterocyclic Chemistry, 2020)
N-heterocyclic carbene (NHC)-based organocatalysis has been widely used for unconventional access to various target molecules. The use of chiral NHCs in the process results in the enantioselective synthesis of various heterocycles. The underlying principle of many of the NHC-catalyzed reactions is the remarkable ability of NHCs to reverse the normal mode of reactivity of aldehydes (umpolung). NHCs can catalyze transformations proceeding via the umpolung or nonumpolung mode for the synthesis of various functionalized molecules. The recent advances in the application of NHCs for the synthesis of various heterocyclic compounds are highlighted in this chapter.
Keywords: aldehyde umpolung; Aldimine umpolung; benzoin reaction; Breslow intermediates; Enantioselective synthesis; Heterocyclic synthesis; N-Heterocyclic carbene; Stetter reaction

Rapid synthesis of zwitterionic phosphonium benzoates by a three-component coupling involving phosphines, arynes and CO2 - Bhattacharjee, Subrata; Raju, Anjali; Gaykar, Rahul N.; Gonnade, Rajesh G.; Roy, Tony; Biju, Akkattu T. (Chemistry-An Asian Journal, 2020)
A mild and easy to perform multicomponent coupling involving phosphines, arynes generated from 2-(trimethylsilyl)aryl triflates, and CO(2)allowing the transition-metal-free synthesis of zwitterionic phosphonium benzoates has been developed. The reaction proceeds via the generation of 1 : 1 zwitterionic intermediates from phosphines and arynes followed by the interception with CO(2)to deliver the carboxylates in moderate to good yields instead of the anticipated benzooxaphosphol-3(1H)-ones.
Keywords: arynes; Carbon dioxide; multicomponent coupling; Phosphines; zwitterions

Enantioselective synthesis of 5,6-dihydroindolizines by N-heterocyclic carbene (NHC)-catalyzed core-structure-inspired strategy of azolium-enolate cascade - Ghosh, Arghya; Shee, Sayan; Barik, Shilpa; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2021)
The core-structure motivated design has allowed the enantioselective synthesis of 5,6-dihydroindolizines via N-heterocyclic carbene (NHC) catalysis. The NHC-catalyzed reaction of alpha,beta-unsaturated aldehydes with the suitably substituted pyrrole derivatives proceed via the initial generation of alpha,beta-unsaturated acylazoliums from enals, and enolates from pyrroles and the reaction culminated in an efficient cascade process involving the Michael-aldol-lactonization-decarboxylation sequence to afford the products in reasonable yields and high selectivities. The method is further extended to the construction of spirocyclic 5,6-dihydroindolizines.

NHC-catalyzed desymmetrization of N-aryl maleimides leading to the atroposelective synthesis of N-Aryl succinimides - Barik, Soumen; Shee, Sayan; Das, Soumik; Gonnade, Rajesh G.; Jindal, Garima; Mukherjee, Subrata; Biju, Akkattu T. (Angewandte Chemie-International Edition, 2021)
Although the construction of axially chiral C-C bonds leading to the atroposelective synthesis of biaryls and allied compounds are well-known, the related synthesis of compounds bearing axially chiral C-N bonds are relatively rare. Described herein is the N-heterocyclic carbene-catalyzed atroposelective synthesis of N-aryl succinimides having an axially chiral C-N bond via the desymmetrization of N-aryl maleimides. The NHC involved intermolecular Stetter-aldol cascade of dialdehydes with prochiral N-aryl maleimides followed by oxidation afforded N-aryl succinimides in good yields and ee values. Preliminary studies on rotation barrier for the C-N bond, the temperature dependence, and detailed DFT studies on mechanism are also provided.
Keywords: asymmetric catalysis; axial chirality; desymmetrization; N-heterocyclic carbenes; organocatalysis

Dynamic kinetic resolution of gamma,gamma-disubstituted indole 2-carboxaldehydes via NHC-Lewis acid cooperative catalysis for the synthesis of tetracyclic epsilon-lactones - Balanna, Kuruva; Barik, Soumen; Shee, Sayan; Gonnade, Rajesh G.; Biju, Akkattu T. (2022)
The ubiquity of epsilon-lactones in various biologically active compounds inspired the development of efficient and enantioselective routes to these target compounds. Described herein is the enantioselective synthesis of indole-fused epsilon-lactones by the N-heterocyclic carbene (NHC)-Lewis acid cooperative catalyzed dynamic kinetic resolution (DKR) of in situ generated gamma,gamma-disubstituted indole 2-carboxaldehydes. The Bi(OTf)(3)-catalyzed Friedel-Crafts reaction of indole-2-carboxaldehyde with 2-hydroxy phenyl p-quinone methides generates gamma,gamma-disubstituted indole 2-carboxaldehydes, which in the presence of NHC and Bi(OTf)(3) afforded the desired tetracyclic epsilon-lactones in up to 93% yield and >99 : 1 er. Moreover, preliminary studies on the mechanism of this formal [4 + 3] annulation are also provided.

Enantioselective synthesis of dihydrothiopyranones via NHC- catalyzed [3+3] annulation of 2-bromoenals with beta-oxodithioesters - Barik, Shilpa; Shee, Sayan; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2022)
The N-heterocyclic carbene (NHC)-organocata-lyzed [3 + 3] annulation of 2-bromoenals with fi-oxodithioesters resulting in the enantioselective synthesis of dihydrothiopyranones is presented. The chiral a,fi-unsaturated acylazoliums generated from 2-bromoenals and carbenes underwent smooth interception with the sulfur nucleophiles to furnish the sulfur heterocycles in satisfactory yields/selectivity. The regioselective formation of dihydrothiopyranones over the competing dihydropyranones is noteworthy.

NHC-catalyzed enantioselective synthesis of tetracyclic δ-lactones by (4+2) annulation of ortho-quinodimethanes with activated ketones - Sarkar, Deeptanu; Barik, Shilpa; Shee, Sayan; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2023)
The N-heterocyclic carbene (NHC)-catalyzed generation of ortho-quinodimethanes (o-QDMs) from 9H-fluorene-1-carbaldehydes followed by the interception with activated ketones resulting in the enantioselective synthesis of tetracyclic delta-lactones is presented. High diastereoselectivity of products, remote C-(sp(3))-H functionalization, broad substrate scope, and mild reaction conditions are the notable features of the present (4 + 2) annulation.

N-heterocyclic carbene-catalyzed atroposelective synthesis of N-N axially chiral 3-amino quinazolinones - Balanna, Kuruva; Barik, Soumen; Barik, Shilpa; Shee, Sayan; Manoj, Niket; Gonnade, Rajesh G.; Biju, Akkattu T. (ACS Catalysis, 2023)
Although the atroposelective synthesisof biaryls and related compoundsbearing axially chiral C-C bonds is well-known, the synthesisof axially chiral C-N bond-containing compounds is relativelyless explored, and the construction of axially chiral N-N bondshas received only scant attention. Demonstrated herein is the N-heterocycliccarbene (NHC)-catalyzed selective amidation reaction, leading to theatroposelective synthesis of N-N axially chiral 3-amino quinazolinones.The NHC-catalyzed reaction of quinazolinones containing a free N-Hmoiety with & alpha;,& beta;-unsaturated aldehydes under oxidativeconditions furnished the atropisomeric quinazolinone derivatives undermild conditions and broad scope. Preliminary studies on experimentaland density functional theory-based N-N rotational barrierdetermination are also presented.
Keywords: amino quinazolinones; asymmetriccatalysis; axial chirality; N-heterocycliccarbenes; organocatalysis